2004
DOI: 10.1111/j.1467-2679.2004.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

From small‐scale habitat loopholes to decadal cycles: a habitat‐based hypothesis explaining fluctuation in pelagic fish populations off Peru

Abstract: The Peru‐Humboldt Current system (HCS) supports the world's largest pelagic fisheries. Among the world's eastern boundary current systems, it is the most exposed to high climatic stress and is directly affected by El Niño and La Niña events. In this volatile ecosystem, fish have been led to develop adaptive strategies in space and time. In this paper, we attempt to understand the mechanisms underlying such strategies, focusing on the El Niño 1997–98 in Peru from which an extensive set of hydrographic, capture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
171
1
12

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(198 citation statements)
references
References 58 publications
14
171
1
12
Order By: Relevance
“…This marine ecosystem is highly susceptible to changes in upwelling patterns, such as alteration in frequency or magnitude (Aravena et al 2014). Significant potential impacts due to climate change have been projected on the spawning rate of small pelagic fish, such as the Peruvian anchovy Engraulis ringens and the sardine Sardinops sagax (Brochier et al 2013), despite the projected temperatures remaining within accepted ecological ranges (Bertrand et al 2004). Small pelagic species strongly depend on zooplankton availability and the exceptional phytoplankton productivity in coastal upwelling zones .…”
Section: Considerations For Marine Life and Fishery Productivitymentioning
confidence: 99%
“…This marine ecosystem is highly susceptible to changes in upwelling patterns, such as alteration in frequency or magnitude (Aravena et al 2014). Significant potential impacts due to climate change have been projected on the spawning rate of small pelagic fish, such as the Peruvian anchovy Engraulis ringens and the sardine Sardinops sagax (Brochier et al 2013), despite the projected temperatures remaining within accepted ecological ranges (Bertrand et al 2004). Small pelagic species strongly depend on zooplankton availability and the exceptional phytoplankton productivity in coastal upwelling zones .…”
Section: Considerations For Marine Life and Fishery Productivitymentioning
confidence: 99%
“…Besides deductive and laboratory evidence, several larger scale empirical studies in the HCS showed an association of anchovy with cold coastal upwelling and mixed upwelling oceanic waters (Bertrand et al 2004, Swartzman et al 2008. Additionally, in the California Current system (CCS), Rykaczewski & Checkley (2008) suggested that high coastal upwelling regimes were associated with higher anchovy production while wind curl generated upwelling, which tends to be weaker, was more associated with sardine dominance.…”
Section: Introductionmentioning
confidence: 99%
“…The persistent stable temperate conditions in a broad range of the Humboldt Current allow larvae to develop all year round (for review see Fischer and Thatje, 2008). As one of the world's most productive ecosystems, the Humboldt Current supports one of the world's largest fisheries (Bertrand et al, 2004) which is of high economical importance for the adjacent countries (Ryther, 1969;Urban and Tarazona, 1996;Food and Agricultural Organization, 2006). The availability of resources is highly dependent on the global coupled ocean-atmosphere phenomenon El Niño Southern Oscillation (ENSO) (Lehodey et al, 2006).…”
Section: Introductionmentioning
confidence: 99%